2006
DOI: 10.1124/dmd.105.007013
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient Repair of Tamoxifen-Dna Adducts in Rats and Mice

Abstract: A long-term treatment with tamoxifen (TAM) to women increases the risk of developing endometrial cancer. The cancer may result from genotoxic damage induced by this drug. In fact, TAM-DNA adducts were detected in the liver of rats treated with TAM and initiated to develop hepatocellular carcinomas. To explore the distribution and repair rate of TAM-DNA adducts, the level of TAM-DNA adducts in all tissues of rats and mice was monitored for 28 days and 7 days, respectively, after the termination of TAM treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Tamoxifen is related to aneuploidy induction and DNA damage in animal hepatocytes (Sargent et al 1994;Kim et al 2006), and human hepatocytes (Kim et al 2005). It is believed that the toxic effect of tamoxifen on hepatocytes is due to the appearance of reactive metabolites during their metabolism (Park et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Tamoxifen is related to aneuploidy induction and DNA damage in animal hepatocytes (Sargent et al 1994;Kim et al 2006), and human hepatocytes (Kim et al 2005). It is believed that the toxic effect of tamoxifen on hepatocytes is due to the appearance of reactive metabolites during their metabolism (Park et al 2005).…”
Section: Introductionmentioning
confidence: 96%
“…The o-quinone resulting from oxidation of the catechol metabolite, 3,4-diOHTAM, can alkylate amino acid residues on proteins, even though the functional significance of the binding of active metabolites of tamoxifen to proteins is still unclear. The o-quinone can cause damage to cellular DNA through generation of reactive oxygen species, and/or alkylation of DNA [4,[21][22][23]. There is now good evidence that -OHTAM plays an important role in the formation of the electrophilic species responsible for tamoxifen-mediated DNA and protein damage ( Fig.…”
Section: Tamoxifen Metabolismmentioning
confidence: 99%
“…Nevertheless the E forms of these adducts predominate [20][21][22][23]. Scarce studies have addressed this topic and consequently many conjugates/adducts were never detected in biological fluids because they have never been specifically looked for yet.…”
Section: Tamoxifen Metabolismmentioning
confidence: 99%
“…With the addition of a hydroxyl group, 4-OH-TAM has been shown to have a higher potency than TAM both in vitro and in vivo corresponding to a higher affinity for the ER (9). Of interest is the effect of 4-OH-TAM in ER-negative tissues, such as the rat (10) and mouse livers (11), where TAM-DNA adducts and 4-OH-TAM-induced DNA adducts have been demonstrated. Moreover, a study by Shibutani et al demonstrated TAM-DNA adduct formation in ER-positive tissues, such as the human endometrium (12).…”
Section: Introductionmentioning
confidence: 98%